Saudi women STEM pioneers: penetrating the mud ceiling - Alghamdi, Amani K. H.; Almazroa, Hiya (Frontiers in Psychology, 2024)
Although researchers actively study women’s experiences in STEM fields, few do so from women’s perspective. We thematically analyzed life narrative semi-structured interview data (46-item open-ended instrument, 90–120 minutes) from N=8 STEM pioneering Saudi Arabian women careerists (mathematics, medicine, and biology) (convenience sample summer 2023). The extremely accomplished participants (all married most with children) averaged 65+ years of age, 40+ years of experience and came from the three largest Saudi provinces. Important factors influencing choosing STEM included personality traits (e.g., deep desire to academically succeed; problem focused); secondary school peer/academic learning experiences; and male family member support, especially fathers. Struggles and challenges (often viewed as opportunities) included the mud ceiling (not glass); male colleagues’ harsh, prejudiced treatment; and unsupportive administration. Participants were research driven and willing to relocate, re-educate, and change directions to establish and advance their career. Succinctly, “Do not feel you are no one because you are a woman. Choose a STEM field you love no matter how many challenges you face. Prove yourself.”